Colheita de cana-de-açúcar queimada associada a sintomas de rinite e marcadores inflamatórios - Trevisan, Iara Buriola [UNESP]; Santos, Ubiratan de Paula; Leite, Marceli Rocha; Ferreira, Aline Duarte [UNESP]; Silva, Bruna Spolador de Alencar [UNESP]; Freire, Ana Paula Coelho Figueira [UNESP]; Brigida, Gabriel Faustino Santa [UNESP]; Ramos, Ercy Mara Cipulo [UNESP]; Ramos, Dionei [UNESP] (Elsevier, 2018)
Introduction: Burnt sugarcane harvesting requires intense physical exertion in an environment with high temperatures and exposure to particulate matter. Objective: To evaluate the effects of burnt sugarcane harvesting on rhinitis symptoms and inflammatory markers in sugarcane workers. Methods: 32 male sugarcane workers were evaluated with questionnaire for rhinitis symptoms, and for inflammatory markers on peripheral blood and nasal lavage, in the non-harvesting, and 3 and 6 months into the sugarcane harvesting period. Weather data and particulate matter fine concentrations were measured in the same day. Results: The particulate matter concentrations in sugarcane harvesting were 27 (23–33 μg/m3), 112 (96–122 μg/m3), and 63 (17–263 μg/m3); 24 h temperatures were 32.6 (25.4–37.4 °C), 32.3 (26.7–36.7 °C) and 29.7 (24.1–34.0 °C) and relative humidities were 45.4 (35.0–59.7%), 47.9 (39.1–63.0%), and 59.9 (34.7–63.2%) in the non-harvesting period, three and 6 months of the harvesting period. The age was 37.4 ± 10.9 years. The prevalence of rhinitis symptoms was significantly higher at 3 months of the harvesting period (53.4%), compared to non-harvesting period (26.7%; p = 0.039) and at 6 months into the harvesting period (20%; p = 0.006). Concentrations of interleukin 6 (IL-6) in nasal lavage increased after 3 months of the harvesting period compared to the non-harvesting period (p = 0.012). The presence of rhinitis symptoms, after 3 months of the harvesting period, was directly associated with blood eosinophils and inversely associated with neutrophils. Conclusions: After 3 months of work in burnt sugarcane harvesting the prevalence of rhinitis symptoms and IL-6 in nasal lavage increased. Furthermore, eosinophil counts were directly associated with the rhinitis symptoms in the period of higher concentration of particulate matter.
Burnt sugarcane harvesting is associated with rhinitis symptoms and inflammatory markers
Keywords: Biomass; Inflammation mediators; Occupational exposure; Particulate matter; Rhinitis